A bi-objective algorithm for a reactive multi-skill project scheduling problem (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The aim of this paper is to present project scheduling problem met in a an industrial context. The focus is mainly to the reactive model. In fact, the predictive case was studied in previous works, and this paper presents a solution for a reactive version of the model studied before. We proposed a linear mathematical model for the problem and then we show that this model cannot be used in practice to the solve problem. Then we present a bi-objectve genetic algorithm proposed to solve this problem. Experiment results are provided also.